Trusting Covid-19 recommendations: The role of experts, markets and governments - Facundo Albornoz; Guillermo Cruces; María Lombardi (Inter-American Development Bank (IDB), 2023)
Do individuals trust experts' advice? Does the sector represented by these experts matter for trust and compliance? Do individuals prefer the public or the private sector for large-scale responses to events such as the pandemic? We answer these questions by means of a large-scale survey on a representative sample of 9,444 respondents from Argentina, Bolivia, Colombia, Ecuador, Mexico, Peru and Uruguay. We study if opinions on risk-mitigating actions against Covid-19 are shaped by expert recommendations and the sectors they represent. We identify an backlash against experts' recommendations that is robust across expert sectors and countries, and more pronounced for recommendations that require more effort to implement. We also find that, even for individuals with a low level of trust in the public sector, there is widespread agreement that governments should be preferred over the private sector to lead the production and distribution of vaccines. Most respondents, even those expressing distrust in governments, believe that governments should get involved in producing the vaccine for Covid-19, either exclusively or in a partnership with the private sector. This result is stronger for the distribution of the vaccine than for its production.
Keywords: I1; I3; H4; 330; Experts; Trust; Public Health; Covid-19